1999
DOI: 10.1021/jo981553j
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Syntheses of N-Boc 2-Substituted Pyrrolidines and Piperidines by Intramolecular Cyclization

Abstract: Asymmetric lithiation-substitutions by n-BuLi/(-)-sparteine with the N-Boc-N-(3-halopropyl)allylamines 1-4 provide the N-Boc-2-alkenylpyrrolidines (S)-5, (S)-6, and (S)-7 in yields of 31-93% with enantiomeric ratios (ers) from 65:35 to 90:10. These reactions are shown to involve an initial asymmetric deprotonation, but the enantiodetermining step is a subsequent asymmetric cyclization under the influence of the chiral ligand. Extension to formation of a piperidine is illustrated by reaction of N-Boc-(4-chlorob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(22 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…To illustrate the overall facile synthetic approach to bicyclic compounds 12 – 15 , the synthesis of diene precursors 8 – 11 is depicted as a general retrosynthetic scheme in Scheme (for details, see the Supporting Information). The syntheses start from readily available allyl bromides and Boc‐protected cinnamylamine …”
Section: Resultsmentioning
confidence: 99%
“…To illustrate the overall facile synthetic approach to bicyclic compounds 12 – 15 , the synthesis of diene precursors 8 – 11 is depicted as a general retrosynthetic scheme in Scheme (for details, see the Supporting Information). The syntheses start from readily available allyl bromides and Boc‐protected cinnamylamine …”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, one can envision the use of a carboxylation of the chiral organolithium reagents of type 2 with ClCO 2 Et for preparing esters of type 1 stereoselectively (Scheme ). Although acyclic heteroatom‐stabilized chiral lithium reagents are well known, non‐stabilized secondary alkyllithiums have been less extensively studied . Recently, we reported that an I–Li‐exchange allows the generation of functionalized secondary alkyllithium reagents bearing remote functionalities (at position 3 or 4) .…”
Section: Methodsmentioning
confidence: 99%
“…The asymmetric lithiation/substitution of N-Boc-N-(3-chloropropyl)-2-alkenylamines 395 by n-BuLi/(−)-sparteine (11) provides (S)-N-Boc-2-(alken-1-yl)pyrrolidines 397 via the allyllithium-sparteine complexes 396 (equation 106) 182,288 . Similarly, the piperidine corresponding to 397 was obtained from the N-(4-chlorobutyl)amine.…”
Section: Enantioenriched 2-substituted Pyrrolidinesmentioning
confidence: 99%